Pengembangan Sistem Informasi Profil Sekolah Berbasis Web Di SDS Islam An-Nur - Fairuz Rifailhusni; Muhammad Ahmad Bachtiar K.; Ravi Ubaydillah Yusuf; Khanif Faozi (CV. Multi Kreasi Media, 2025)
The problem of the absence of a school Web Profile Information System at SDS Islam An-Nur is the lack of information delivery to student, parents, and the wider community. In today’s digital era, the need for fast and structured information delivery is very important, but SDS Islam An-Nur still experiences limitations in the aspect of information digitalization. Therefore, this system is designed to present school profile data, activity, gallaries, and school agendas comprehensively and interactively. The technologies used include React.js for the user interface, Tailwind CSS for responsive design, and Node.js and Express.js for server management and MySQL as a database. Data collection was carried out thtough direct observation, interviews with the school, and literature studies, the implementation results show that the system is able to present school information more efficiency, attractiverly, and structured, and facilitate communication between the school and its stakeholders. With the presence of the system, SDS Islam An-Nur can improve the quality of information services, strengthen the school’s image as an institution that is adaptive to technological devlemopment, and support the process of promoting and transparency of educational information in the community.